Comparative Wood Anatomy of Twelve Woody Plant Species in Northeastern Mexico and Its Relation to Taxonomy and Wood Quality - Humberto Gonzalez Rodriguez; Ratikanta Maiti; Jeff Christofher Gonzalez Diaz (International Journal of Economic Plants)
The present study has been undertaken on wood anatomy of 12 woody species at Linares, northeast Mexico. The results show large variation among species in wood anatomical traits such as porosity, vessel diameter, its distribution, parenchyma, compactness of ground tissues and fibre cell characteristics. Most of the species are ring to semiring porous viz., Acacia shaffneri, Acacia wrightii, and Eysenhardtia polystachya. Fibre cell characteristics also showed large variations in morphology, size, and lumen breadth. Most of the species have narrow vessels, viz., Acacia shaffneri, Acacia wrightii, Helietta parvifolia, contained medium sized vessels. Many of the species possess narrow vessels which although impose transport of water but protect the vessels against cavitation during drought and freezing and the species with small narrow vessels mentioned have strategy to adapt both to hot and cold climate against cavitation. All these wood anatomical traits could be utilized to distinguish species as well as quality determinations of species. The variation in hydraulic systems determines the capacity of water transport among species. Besides, these variations in wood anatomical traits such as wood compactness, high density of thick walled wood fibres could be related to good quality of timber for fabrication of strong furniture, on the other hand, the species having broad lumen and thin cell wall could produce good paper pulp which should be confirmed in future study.